2019
DOI: 10.17816/jowd68335-40
|View full text |Cite
|
Sign up to set email alerts
|

Application possibilities of biguanides for fibrocystic breast disease in women of reproductive age

Abstract: Hypothesis/aims of study. The ongoing global problem of health care and medical science is an associated increase in the frequency of endocrine and metabolic diseases and cancer, including in women of childbearing age. Thus, the frequency of diabetes in the population has been growing rapidly for many years. Similar trends were observed in the dynamics of the frequency of cancer pathology, especially of breast cancer, which is one of the leading places in the structure of the cancer incidence in the female pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…We also found two studies that evaluated the effect of MF on FCD disorder in insulin-resistive and non-insulin-resistive patients that showed the positive effect of MF in the management of FCD in these patients [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found two studies that evaluated the effect of MF on FCD disorder in insulin-resistive and non-insulin-resistive patients that showed the positive effect of MF in the management of FCD in these patients [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding benign nature of FCC in association with its slow growth, close observation of the lesion beside therapy of symptoms is considered as the first line of treatment. To date, various herbal and synthetic medications like evening primrose oil; vitagnus; vitamins including D, E, and B; probiotics; metformin; and antioxidant agents have been introduced for prevention of symptoms in FCC, although there is no general consensus on any [ 1 , 6 , [9] , [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, identifying suitable medication with sufficient potency to control such pain could be interesting and helpful to recover patients. Based on previous studies that have demonstrated NAC could act as sulfhydryl group donor, restore glutathione, scavenge free radical, and also regulate production of sex hormones including estrogen and progesterone, we hypothesized that NAC could positively change oxidative stress reactions leading to inflammation and following FCC formation [ [8] , [9] , [10] , [11] , [12] ]. According to this hypothesis, this study aims to investigate possible effects of NAC on pain and biochemical parameters related to FCC.…”
Section: Introductionmentioning
confidence: 99%